Epigenome-wide association study of chronic obstructive pulmonary disease and lung function in Koreans. (July 2017) - Lee, Mi Kyeong; Hong, Yoonki; Kim, Sun-Young; Kim, Woo Jin; London, Stephanie J
Aim: To identify differentially methylated probes (DMPs) and regions (DMRs) in relation to chronic obstructive pulmonary disease (COPD) and lung function traits.Methods: We performed an epigenome-wide association study of COPD and spirometric parameters, including forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC) and FEV1/FVC, in blood DNA using the Infinium HumanMethylation450 (n = 100, a Korean COPD cohort).Results: We found one significant DMP (cg03559389, DIP2C ) and 104 significant DMRs after multiple-testing correction. Of these, 34 DMRs mapped to genes differential expressed with respect to the same trait. Five of the genes were associated with more than two traits: CTU2, USP36, ZNF516, KLK10 and CPT1B .Conclusion: We identified novel differential methylation loci related to COPD and lung function in blood DNA in Koreans and confirmed previous findings in non-Asians. Epigenetic modification could contribute to the etiology of these phenotypes.